The Effect of Problem Based Learing (PBL) Learning Model and Learning Independence on Problem Solving Ability of Ali Bin Abu Talib Integrated Islamic Junior High School Students Deli Serdang - Mariyati, Mariyati; Wijaya, Candra; Anas, Nirwana (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to determine and describe: (1) the effect of the application of the Problem Based Learning (PBL) learning model on the problem solving ability of IT Ali Bin Abu Talib Deli Serdang Junior High School students, (2) the effect of learning independence on the problem solving ability of IT Ali Bin Abu Talib Deli Serdang Junior High School students, and (3) the interaction between learning models and learning independence on the problem solving ability of IT Ali Bin Abu Talib Deli Serdang Junior High School students. This type of research uses a quantitative approach with an experimental model. The population of this research is all students of class VIII of Ali Bin Abu Talib IT Junior High School which consists of two classes. The sampling technique that will be used in this study is total sampling. Total sampling is the same sampling technique as the population. Data collection instruments are questionnaires and tests. Normality testing using Liliefors and homogeneity testing using Bartlett. The data analysis technique is two-way analysis of variance at = 0.05. The results showed: (1) there is an effect of the application of learning models on problem solving ability, this is evident from the results of statistical testing which shows Fhitung = 242.4 > Ftable 3.972, (2) there is an effect of learning independence on problem solving ability, this is evident from statistical testing which shows Fhitung = 183.8 > Ftable 3.972, and (3) there is an interaction between learning models and learning independence, this is evident from statistical testing which shows Fhitung = 86.3 > Ftable 3.972.